Economic Efficiency and Internal Competitive Advantages of Grain Production in the Central Region of Ukraine (Agricultural Engineering, 2021)
The paper discusses competitiveness of the agro-industrial sector, which is a multifaceted concept that characterizes its ability to compete in both domestic and foreign markets. Ukraine has significant opportunities to develop the agricultural sector and turn it into a highly efficient branch of economy. Favorable soil and climate conditions, and fertile land contribute to its further development, obtaining agricultural crops in volumes sufficient to meet domestic needs and build export potential. The production process of agricultural goods takes longer than in industry. Therefore, at the stage of determination of the production program of an agricultural enterprise, it is very difficult to respond on time to changes in consumer demand and increase the product competitiveness within the already established production schemes in the markets. Therefore, the purpose of our study is to evaluate the effectiveness of growing the studied crops in a typical farm in Central Ukraine and offer a roadmap for making management decisions when planning a production program. For this purpose, a method based on calculations of the gross margin, total expenses, production thresholds, profitability, and payback of production factors was chosen.